Cellular toxicity of calcium propionate in human lymphocyte : Cellular toxicity of calcium propionate - Pongsavee, Kritpipat; Pongsavee, Malinee (Cellular and Molecular Biology, 2024)
Calcium propionate is the chemical substance added to food in order to prolong the shelf-life of factory made foods by inhibiting the development of bacteria, fungi and other microorganisms. The objective of this study was to investigate the ability of calcium propionate to induce cytotoxic and genotoxic effects in lymphocytes. Oxidative stress induction by calcium propionate was also studied. Four concentrations of calcium propionate (0.5, 1.0, 1.5 and 2.0 mg/ml) were applied in lymphocytes for 24 and 48 h treatment. It studied cytotoxic and genotoxic effects by MTT assay, chromosome culture technique, and micronucleus assay. Oxidative stress induction was studied by superoxide dismutase (SOD) activity assay. The results showed that lymphocyte viability was decreased significantly by calcium propionate at 1.5 and 2.0 mg/ml (p < 0.05). Calcium propionate induced chromosome aberration at 1.0, 1.5 and 2.0 mg/ml and sister chromatid exchange at 1.5 and 2.0 mg/ml (p < 0.05). It induced micronucleus formation at 0.5, 1.0, 1.5 and 2.0 mg/ml (p < 0.05). The calcium propionate concentrations of 0.5 - 1.0 mg/ml and 1.5 - 2.0 mg/ml could reduce SOD activity inhibition (p < 0.05). Calcium propionate induced oxidative stress in lymphocytes. It can be concluded that calcium propionate induces genotoxic risk and oxidative stress in lymphocytes. Based on this study and the positive results, consumers should be made aware that calcium propionate should be considered a genotoxic compound. The awareness of food preservative usage and the educational program must take place frequently for good human health in the community.